2021
DOI: 10.1071/wf20069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moisture content and thermal behaviour on the ignition of

Abstract: Fuel moisture content is one of the key parameters controlling the flaming ignition of wildland fuel. However, the role of fuel moisture content in assessing the flammability of different fuel curing (dead and live fuel) is still not well understood. This paper presents the results of ignition tests of fuel beds consisting of dead and live Eucalyptus saligna leaves under a wide range of moisture contents. External heat flux and fuel moisture content are shown to significantly influence time to ignition and mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…As expected, increasing the moisture content and thickness of foliage increases the ignition time of live fuels [17][18][19][20][21]. Moisture evaporating from fuels can impact burning by diluting flammable pyrolyzates (i.e., gas around the live fuel), absorbing thermal energy, possibly altering combustion reactions, and ultimately delaying the time to ignition in dead and live fuels [11,[17][18][19][20][21][22]. In some instances, live fuels have displayed blistering on the surface of the fuel, droplet ejection, or bursting of the structure while burning [19][20][21][22].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…As expected, increasing the moisture content and thickness of foliage increases the ignition time of live fuels [17][18][19][20][21]. Moisture evaporating from fuels can impact burning by diluting flammable pyrolyzates (i.e., gas around the live fuel), absorbing thermal energy, possibly altering combustion reactions, and ultimately delaying the time to ignition in dead and live fuels [11,[17][18][19][20][21][22]. In some instances, live fuels have displayed blistering on the surface of the fuel, droplet ejection, or bursting of the structure while burning [19][20][21][22].…”
Section: Introductionmentioning
confidence: 71%
“…As a result, many studies have investigated the influence of LFMC on the flammability of fuels. As expected, increasing the moisture content and thickness of foliage increases the ignition time of live fuels [17][18][19][20][21]. Moisture evaporating from fuels can impact burning by diluting flammable pyrolyzates (i.e., gas around the live fuel), absorbing thermal energy, possibly altering combustion reactions, and ultimately delaying the time to ignition in dead and live fuels [11,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The relationship between FMC and ignitability seems to be linear, with higher FMC leading to longer time to ignition (i.e., reduced flammability) [40]. Researchers [51] found that higher FMC in fresh leaves and dead leaves (i.e., litter) led to reduced ignitability regardless of the intensity of the heat flux. Specifically, it was found that fresh eucalypt leaves required significantly higher temperatures of ignition (472 • C vs. 377 • C) and heat fluxes (24.5 kWm −2 vs. 15.5 kWm −2 ) when compared with dry leaves.…”
Section: MCmentioning
confidence: 99%